2006
DOI: 10.1016/j.ydbio.2006.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Cellular electroporation induces dedifferentiation in intact newt limbs

Abstract: Newts have the remarkable ability to regenerate lost appendages including their forelimbs, hindlimbs, and tails. Following amputation of an appendage, the wound is rapidly closed by the migration of epithelial cells from the proximal epidermis. Internal cells just proximal to the amputation plane begin to dedifferentiate to form a pool of proliferating progenitor cells known as the regeneration blastema. We show that dedifferentiation of internal appendage cells can be initiated in the absence of amputation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…In addition, the mouse myotubes that responded to the newt regeneration extract were cleaved into smaller myotubes or proliferative mononucleated cells, indicating that even the myofibers that have both the nuclei reentering the cell cycle and remaining in the quiescent state may be able to dedifferentiate after electroporation. While the electroporation to newt limbs induces cell cycle reentry of nuclei within skeletal muscle tissues, regardless of the presence of plasmid DNA [3], the present study showed that plasmid DNA is essential to the cell cycle reentry of nuclei within myofibers after electroporation. This indicates that the presence or the expression of plasmid DNA can influence the cell cycle reentry of myonuclei of mammals.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…In addition, the mouse myotubes that responded to the newt regeneration extract were cleaved into smaller myotubes or proliferative mononucleated cells, indicating that even the myofibers that have both the nuclei reentering the cell cycle and remaining in the quiescent state may be able to dedifferentiate after electroporation. While the electroporation to newt limbs induces cell cycle reentry of nuclei within skeletal muscle tissues, regardless of the presence of plasmid DNA [3], the present study showed that plasmid DNA is essential to the cell cycle reentry of nuclei within myofibers after electroporation. This indicates that the presence or the expression of plasmid DNA can influence the cell cycle reentry of myonuclei of mammals.…”
Section: Discussionsupporting
confidence: 47%
“…Atkinson et al showed that electroporation to newt appendages and tail induces cell cycle reentry of nuclei within skeletal muscle tissue, and raised the possibility of dedifferentiation of myofibers [3]. In the regenerative process following amputation of newt appendages, not only the myonuclei but also the nuclei of activated satellite cells, which are separated from myofibers by sarcolemma [9], reenter the cell cycle [7,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic analysis suggests that reduced metabolic activity, up-regulation of the unfolded protein response (UPR), and differential regulation of apoptotic pathways may largely prevent apoptosis of limb cells (Rao et al, 2009), which is known to be minimal during blastema formation (Mescher et al, 2000;Atkinson et al, 2006). Studies on cultured chondrocytes, b-cells, and Muller glia cells of the retina suggest that cells dedifferentiate as part of a mechanism to combat apoptotic cell stress (for discussion, see Rao et al, 2009).…”
Section: Mechanisms Of Histolysis and Dedifferentiationmentioning
confidence: 99%
“…Transgenesis is possible (Sobkow et al, 2006) but is relatively inefficient, suffers from the long generation time of the axolotl, and has only recently been coupled with any induction system (Whited et al, 2012) or tissue-specific promoters (Monaghan and Maden, 2012). Electroporation is currently the predominant means with which to mis-express genetic elements in salamanders (Berg et al, 2010;Echeverri and Tanaka, 2002;Echeverri and Tanaka, 2003;Echeverri and Tanaka, 2005;Kumar et al, 2007;Mercader et al, 2005), yet this method has drawbacks, such as dilution of plasmid with cell division, and the procedure itself has been shown to cause some degree of cellular dedifferentiation in newts (Atkinson et al, 2006) akin to the dedifferentiation that is a hallmark of limb regeneration.…”
Section: Introductionmentioning
confidence: 99%